Is surgical intervention more effective than non-surgical treatment for acute Achilles tendon rupture? A systematic review of overlapping meta-analyses. (December 2016) - Wu, Yaohong; Lin, Linghan; Li, Hao; Zhao, Yachao; Liu, Longgang; Jia, Zhiwei; Wang, Deli; He, Qing; Ruan, Dike
Abstract: Objective: There is discordance in the results from meta-analyses on surgical versus non-surgical treatment for acute Achilles tendon rupture. We systematically reviewed the overlapping meta-analyses on this topic to provide information that will be helpful to decision makers when selecting treatments based on the current best available evidence. Methods: We comprehensively searched multiple databases for systematic reviews that compared surgical and non-surgical treatments for acute Achilles tendon rupture. We only included meta-analyses that comprised randomized controlled trials (RCTs). The methodological quality and extracted data were assessed. The meta-analysis that offered the best evidence was ascertained with the Jadad decision algorithm. Results: Nine meta-analyses were included in our study and all of them included RCTs with Level-II evidence. Assessment of Multiple Systematic Reviews (AMSTAR) scores ranged from 5 to 10 (median 7). The Jadad decision algorithm was used to select a high-quality meta-analysis with more RCTs. The results from this study showed that when functional rehabilitation was used, non-surgical intervention was similar to surgical treatment regarding the incidence of range of motion, rerupture, calf circumference and functional outcomes, and the incidence of other complications was reduced. Non-surgical intervention significantly increased the rerupture rate if functional rehabilitation was not considered. Conclusions: The findings of meta-analyses regarding surgical versus non-surgical treatment for acute Achilles tendon rupture are inconsistent. According to this systematic review of overlapping meta-analyses, the current best available evidence suggests that centers offering functional rehabilitation may prefer non-surgical intervention. Surgical treatment may be preferred at centers that do not have functional rehabilitation. Highlights: Rehabilitation protocol may influence relative effects of surgical and non-surgical treatments for acute Achilles tendon rupture. Centers offering functional rehabilitation may prefer non-surgical intervention. Surgical treatment may be preferred at centers that do not have functional rehabilitation.